REAKTUALISASI FUNGSI BALE BANJAR DI KOTA DENPASAR - Putu Suryawati (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
This article discusses the re-actualization of the Bale Banjar function in Denpasar City. In the current era of modernization, especially the banjars located in the City of Denpasar displays a different face. The rapid growth of the population, the high demand for the economic space due to the emergence of capitalist economy, the change of mindset of the society from agrarian society to industrial society with high production demands have made the banjars experiencing functional re-actualization. The topic of re-actualization of the bale banjar function will be discussed with the approach of sociology, using data collection techniques from observation, interview and document study.